HUBUNGAN NILAI VO2 MAX DAN INDEKS MASSA TUBUH PADA ATLET NTB - Dian Rahadianti (Nusantara Hasana Berdikari, 2022)
Physical fitness level can reflect a person's aerobic capacity which can be measured by calculating the maximum volume of oxygen used during exercise (VO2 Max). Good athlete performance is characterized by a high VO2 Max value. Body Mass Index (BMI) is one of the indicators in determining nutritional status and has a close relationship with a person's physical fitness. This study aims to see the relationship between BMI and the value of VO2 Max. This study is a cross-sectional study of 88 athletes from the NTB Regional Training Center in June 2021. BMI value is measured by weight and height. The VO2 max value was assessed using the Beep Test. The data were analyzed using the Spearman rank test and the results were significant if the p-value <0.05. Most athletes have a normal BMI (78.4%) and have a VO2 max value in the good category (62.5%). There is a significant relationship between the value of VO2 Max with BMI (p = 0.000). A person's level of physical fitness as indicated by the VO2 Max value will be higher as the BMI decreases.